Another Look at the PERT Assumptions - Kotiah, T. C. T.; Wallace, N. D. (Management Science, 1973)
A maximum entropy approach leads to a truncated normal distribution for the activity time in PERT analysis. Three different methods of fit are discussed, and a comparison with the standard assumption of a Beta distribution is made. The results suggest new ways of performing the PERT analysis.